Influência do uso da terra e precipitação pluviométrica em variáveis limnológicas da bacia hidrográfica do rio Ibicuí da Armada-RS. - Dal Osto, Janderlei Velasque (2019)
The Ibicuí da Armada River Basin - BHRIA is located in the southwest portion of Rio Grande do Sul. With an area of approximately 6,006.7 km² it extends over the municipalities of Rosário do Sul, Dom Pedrito and Santana do Livramento. The objective of the research was to analyze the relationship between limnological variables, precipitation data and the various land uses within the study area. The methodology consisted of the acquisition of SENTINEL 2 satellite images to generate land use maps using bands 2,3,4 and 8. The land use classes generated were: agricultural activity, field, exposed soil, forest, water and urban area. The limnological variables analyzed were: water temperature, transparency, hydrogen potential, electrical conductivity, total suspended solids and turbidity. For the acquisition of limnological data, 17 field missions were carried out at 2 points within the watershed between October 2018 and April 2019, one closer to the urban area of Rosário do Sul and one to another. a little further away, on the border of the municipality with Santana do Livramento. For a more complete analysis, rainfall data were obtained from 3 meteorological stations, two of them belonging to the National Institute of Meteorology (São Gabriel - A832 and Santana do Livramento - A804) and one from the National Center for Natural Disaster Monitoring and Alerts (Serra do Caverá Station). With the acquired data, an arithmetic mean was performed, seeking a better characterization of the study area. The land use maps showed the changes between November 2018 and March 2019, mainly with regard to agricultural areas, since the study area has its economic base in agriculture, and these changes between agricultural stages, Soil preparation, planting and harvesting significantly influenced limnological variables, mainly suspended solids and turbidity. Through statistical analysis it was possible to realize the influence of rainfall on limnological variables, especially on electrical conductivity, and an important factor regarding rainfall in the study area during the analysis period was a moment of extreme precipitation, which occurred in January, where the average rainfall was above 400 mm, causing a flood event on the Ibicuí da Armada River. Other variables that showed a statistically significant correlation were electrical conductivity with pH and also Turbidity with Total Suspended Solids (TSS). Thus, the results of the present study underscore the importance of the acquisition, knowledge and data generation about water resources, seeking a better preservation of the environment.